Free software as a necessary element for the democracy of the crowd - Many, Gabriel (2016)
Antonio Negri and Michael Hardt's Empire and Multitude propose that Empire is the dominant controlling force of the contemporary capitalism. The force of Empire is in its ability to control intellectual production, a power which has been increasing during the transition period of the capitalist model. This essay proposes that those oppressed by Empire -that is the Multitude as a class-, need free software as a means to fulfill this class's dream of democracy. Software is the best example of how democracy could be; it is also a tool for enhancing democracy. Given the weakness of Empire's model of liberal democracy within the Andean Region, the potential that free software affords is even greater.